MODIFIED TREATMENT OF SHALLOW FORNIX FOR BETTER RETENTION OF OCULAR PROSTHESIS - Kamil, Zeeshan; Qurban, Qirat; Khan, Muhammad Tanweer Hassan (Journal of Ayub Medical College Abbottabad, 2022)
Background: The purpose of this study is to share the experience of a modified surgical technique for treating shallow inferior fornix to enhance the retention of cosmetic ocular prosthesis in a tertiary care hospital. It was a Quasi experimental study, carried out at Khalid Eye Hospital, Karachi, Pakistan from January to December 2018. Methods: This study included twenty-five patients between the ages of 20-40 years belonging to either gender having an anophthalmic socket with shallow inferior fornices unable to retain cosmetic ocular prosthesis. Three pieces of Silicone tube were placed deep within the inferior fornix with the help of 2-0 Vicryl suture, taking bite of the inferior orbital rim periosteum. Main outcome measure was deepening of the inferior fornix with better retention of the ocular prosthesis. All the patients were followed up for a period of one year after the surgery. Study dynamics were briefed to all the patients and study approval obtained from the hospital ethical review committee. Results: This study included a total of twenty five patients of both genders. Mean age was 29.6±6.53 years. By the end of the follow up period, twenty-four (96%) out of the twenty-five patients were satisfied with a proper retention of ocular prosthesis within the fornix along with complete lid closure. One (4%) patient required revision surgery because of extrusion of the silicone tube piece after one month. Mean follow up period was 358.5±16.76 days. Conclusion: This modified technique does not require expensive consumables and proved to be effective in terms of cosmetic and functional outcome.